A new community for those involved and interested in diagnosis and prognosis. Issue 1 (December 2017) - Moons, Karel; Cook, Nancy; Collins, Gary
Abstract Why do we need a new journal titledDiagnostic and Prognostic Research in the year 2017, in an era where communication has shifted towards instant messaging via avenues such as Twitter, blogs and Facebook and where we already have tens of thousands of biomedical journals, producing millions of papers, editorials and letters each year?